Diol-Based Polymer Microparticles for Treatment of Cutaneous Aspergillosis in an Immunocompromised Murine Model. (4th October 2017) - Tatara, Alexander; Albert, Nathaniel; Watson, Emma; Mikos, Antonios; Kontoyiannis, Dimitrios P
Abstract: Background: Local delivery of antifungals may allow for high concentrations of therapeutic directly in wound beds infected with invasive fungi. In this work, microparticles (MPs) fabricated from a novel biodegradable polymer synthesized from 1, 10-decanediol (DD) and fumaric acid were leveraged for the local delivery of voriconazole (VRC) in a murine model of cutaneous aspergillosis. In addition to controlled local delivery of VRC, the MPs also degrade into byproducts which themselves have bioactivity against fungal viability and promote host wound healing. Methods: The in vitro release kinetics of VRC-loaded MPs were measured over 6 days in PBS at 37 o C under mild agitation. Immunocompromised BALB/c mice with 5 mm full thickness cutaneous defects infected with A. fumigatus were treated with: Group 1) no infection, no treatment; Group 2) no treatment; Group 3) unloaded blank MPs; and Group 4) VRC-loaded MPs ( n = 10 per group). Six days after treatment (nine days after initial infection), mice were euthanized. Wound bed size, fungal wound bed CFU, and histological presence of fungi were evaluated to determine the effects of MPs on wound healing and infection. Results: MPs were capable of releasing VRC at concentrations above A. fumigatus MIC for at least six days. Mice treated with VRC-loaded MPs had significantly decreased wound size than mice with no treatment (64.2% vs. 19.4% wound reduction, P = 0.002) and were not significantly different than uninfected controls (64.2% vs. 58.1%, P = 0.497). Although wound healing was increased with VRC-loaded MPs, total fungal burden was not significantly different between infected groups. Conclusion: Diol-based MPs are capable of local delivery of VRC to treat infected wound beds in an immunocompromised murine model of cutaneous aspergillosis. VRC-loaded MPs restored normal wound healing. As fungal burden was unchanged, the exact mechanism of enhanced wound healing needs to be further explored. Disclosures: D. P. Kontoyiannis, Pfizer: Research Contractor, Research support and Speaker honorarium; Astellas: Research Contractor, Research support and Speaker honorarium; Merck: Honorarium, Speaker honorarium; Cidara: Honorarium, Speaker honorarium; Amplyx: Honorarium, Speaker honorarium; F2G: Honorarium, Speaker honorarium